Illocutionary Speech Acts in the Tobus Huning Ceremony of the Batak Simalungun Ethnic Group and the Regional Language Lesson Plan - Tampubolon, Flansius; Purba, Roma Hotni Uhur; Tambunan, Abel Rotua; Hutagalung, Adreas; Pandiangan, Johannes (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to describe and analyze the types of illocutionary speech acts that emerge during the Tobus Huning ritual in the Batak Simalungun community. Tobus Huning is a sacred rite within the traditional wedding ceremony that holds symbolic meaning as a form of respect and gratitude to parents—particularly the mother—for their sacrifices in raising a child until marriage. This ritual functions not only as a customary formal procedure but also serves as a medium for emotional expression and the intergenerational transmission of cultural values. This research employs a descriptive qualitative approach, with data collected through participatory observation of the ritual, audiovisual documentation, and in-depth interviews with traditional leaders, the families of the bride and groom, and local cultural stakeholders. Data analysis was carried out in three stages: data reduction, data display, and conclusion drawing through an inductive process. The findings indicate the presence of four dominant types of illocutionary acts: (1) Assertives, used to convey information and symbolic interpretations of each ritual stage; (2) Directives, functioning as instructions or requests to ensure the ceremony proceeds according to customary norms; (3) Expressives, articulating emotions such as gratitude, reverence, and heartfelt sentiments among family members; and (4) Commissives, which contain promises and moral commitments made by the bride and groom to their parents and extended families. These findings affirm that speech acts in the Tobus Huning ritual not only serve pragmatic functions of communicative intent but also act as an essential medium for preserving cultural identity, transmitting spiritual values, and reinforcing social solidarity within the Batak Simalungun community.